Resistance to Change as a Mediator Between Conscientiousness and Teachers’ Job Satisfaction. The Moderating Role of Learning Goals Orientation - Paloş, Ramona; Vîrgă, Delia; Craşovan, Mariana (Frontiers in Psychology, 2022)
Teachers’ job satisfaction has been the subject of many studies that tried to identify its main sources. Based on the social cognitive career theory (Lent et al., 1994), the present study aimed to investigate the relationships between personality traits, goals orientation, and teachers' job satisfaction. 321 Romanian teachers completed an online questionnaire. The results demonstrated new insights regarding the relationships between psychological variables (conscientiousness, dispositional resistance to change, achievement goals orientation) and teachers’ job satisfaction. Cognitive rigidity, as a mechanism to resistance to change, mediates between conscientiousness and teachers' job satisfaction. Moreover, the moderation role of learning goals orientation manifests in the relation between conscientiousness and job satisfaction. These findings emphasize that school management needs to offer teachers information and explain the change's benefits if they want to prevent individual resistance to change and decrease satisfaction related to their work.